Autism spectrum disorder and celiac disease: no evidence for a link - Icaro Camargo Batista; Lenora Gandolfi; Yanna Karla Medeiros Nobrega; Rodrigo Coutinho Almeida; Lucas Malta Almeida; Dioclécio Campos Junior; Riccardo Pratesi (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the possible association between celiac disease (CD) and/or gluten sensitivity (GS) and autism spectrum disorder (ASD). METHODS: Occurrences of CD were determined in a group of children and adolescents affected by ASD and, conversely, occurrences of ASD were assessed in a group of biopsy-proven celiac patients. To detect the possible existence of GS, the levels of antigliadin antibodies in ASD patients were assessed and compared with the levels in a group of non-celiac children. RESULTS: The prevalence of CD or GS in ASD patients was not greater than in groups originating from the same geographical area. Similarly the prevalence of ASD was not greater than in a group of biopsy-proven CD patients. CONCLUSION: No statistically demonstrable association was found between CD or GS and ASD. Consequently, routine screening for CD or GS in all patients with ASD is, at this moment, neither justified nor cost-effective.